#### inspirational_godess

##### New member

- Joined
- Aug 31, 2006

- Messages
- 3

Problem:

4x - 3(y - 2) = 15 + y

how do u rewrite an equatio so that X is a function of Y. (show all steps)

Problem:

5y - 2(x - 7) = 20

- Thread starter inspirational_godess
- Start date

- Joined
- Aug 31, 2006

- Messages
- 3

Problem:

4x - 3(y - 2) = 15 + y

how do u rewrite an equatio so that X is a function of Y. (show all steps)

Problem:

5y - 2(x - 7) = 20

What does "u" mean? A variable?inspirational_godess said:how do u rewrite an equation in function form, so that Y is a function of X. (show all steps)

and

how do u rewrite an equatio so that X is a function of Y. (show all steps

4x - 3(y - 2) = 15 + y

4x = 15 + y + 3(y - 2) : do you understand that?

3(y - 2) = 3y - 6 : do you understand that?

If not, not much can be done here: not a classroom.

- Joined
- Feb 4, 2004

- Messages
- 15,943

Solve the equation for "y=".inspirational_godess said:how do u[sic] rewrite an equation in function form, so that Y is a function of X[?]

In general, solve the equation for "(function name) = (something with the other variable)". For instance, given "3s + 4t = 6", one could do the following:

. . .Solve for s as a function of t:

. . . . .3s + 4t = 6

. . . . .3s = 6 - 4t

. . . . .s = 2 - (4/3)t

. . .Solve for t as a function of s:

. . . . .3s + 4t = 6

. . . . .4t = 6 - 3s

. . . . .t = (3/2) - (3/4)s

Follow this procedure with your exercises. If you get stuck, please reply showing how far you have gotten. Thank you.

Eliz.

- Joined
- Aug 31, 2006

- Messages
- 3

It really helped. thank you. i took the test today and i think i pretty much aced it.

- Joined
- Feb 4, 2004

- Messages
- 15,943

Congratulations!inspirational_godess said:i took the test today and i think i pretty much aced it.

Eliz.